Caso hematológico - Lopes,Raquel (2011)
Essential Thrombocythemia (ET) is a rare disease in pediatric age. The dominant clinical manifestations are thrombotic (arterial or venous) and/or hemorrhagic, but most of the cases are asymptomatic, and diagnosis made by routine hemogram. A previously healthy adolescent, federated football player, was oriented to the paediatric haematology consultation, at the age of 15 years, because of the presence of sustained thrombocytosis. It was established the diagnosis of Essential Thrombocythemia based on the criteria of the World Health Organization (WHO) 2008. The authors highlight the importance of establishing this diagnosis, even in pediatric age, to set the earliest possible a strategy of clinical surveillance, prevention of associated complications and the most adequate therapeutic approach.